Motuotrichius yangi, a new genus and species from southeastern Tibet, China (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini) - Huang, Hao; Chen, Chang-Chin (Zootaxa, 2016)
Motuotrichius yangi, new genus, new species is described from Motuo, southeastern Tibet. Motuotrichius seems to have a mixture of characters observed in the genera Epitrichius Tagawa, 1941, Indotrichius Krikken, 2009, Lasiotrichius Reitter, 1899, and Trichius Fabricius, 1775, but is separable from all the known Eurasian genera of Trichiina by the presence of a tooth on the inner side of the mesotibia in both sexes. The habitus, external characters, and male genitalia of Motuotrichius yangi are illustrated. The following new combinations are given: Gnorimotrichius albomaculatus (Moser, 1902), Gnorimotrichius signatus (Chûjô, 1940), Gnorimotrichius trilineatus (Ma, 1992), and Gnorimotrichius tronqueti (Antoine, 2002).